Complications and outcomes of salvage robot‐assisted radical prostatectomy: a single‐institution experience. (May 2014) - Yuh, Bertram; Ruel, Nora; Muldrew, Shantel; Mejia, Rosa; Novara, Giacomo; Kawachi, Mark; Wilson, Timothy
Abstract : Objective: To determine the peri‐operative outcomes of men undergoing salvage robot‐assisted prostatectomy (RARP) and to examine the complications, functional consequences and need for additional treatments after salvage RARP. Patients and Methods: At total of 51 consecutive patients underwent salvage RARP after previous failed local therapy. Biochemical recurrence (BCR) was defined as two postoperative PSA measurements ≥0.2 ng/mL. Complications at any time postoperatively were recorded prospectively using a modified Clavien system. The Kaplan–Meier method was used for survival estimation, and regression models were used to identify the predictors of BCR or progression‐free survival (PFS) and complications. Results: The median age at salvage RARP was 68 years and a median of 68 months had elapsed from the time of primary treatment. The median follow‐up was 36 months. The median operation duration was 179 min with a median estimated blood loss of 175 mL. In all, 50% of patients had pathological stage 3 disease and positive surgical margins were found in 31% of patients. The estimated 3‐year BCR‐free or PFS was 57%. The overall complication rate was 47%, with a 35% major complication rate (Grade III–V). Potency was maintained in 23% of preoperatively potent patients and 45% of all patients regained urinary control. No clinical variables were predictive of major complications, but all patients with postoperative bladder neck contracture were incontinent. A higher PSA level and extracapsular extension were significantly associated with BCR or progression ( P < 0.01). Conclusions: Salvage RARP provides oncological control with potential avoidance of systemic non‐curative therapy. Complication, incontinence and erectile dysfunction rates are significant but frequently correctable. This reinforces the need for proper patient counselling and selection.